1968
DOI: 10.1002/j.2333-8504.1968.tb00996.x
|View full text |Cite
|
Sign up to set email alerts
|

Stylistic Factors in Learning and Retention

Abstract: The purposes of this investigation were, first, to determine the extent of individual consistency in the tendencies to err either by omission or commission in tasks requiring learning and retention, and, secondly, to determine the relationship between any such consistent tendencies and relevant cognitive, personality, and ability variables. A battery of 26 tests from which 86 variables were generated was administered to 147 college students, 70 men and 77 women, by individual and group testing. Information con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 130 publications
0
8
0
Order By: Relevance
“…In contradiction to Gollin and Baron, a dissertation study appeared at about the same time in which savings scores on relearning under conditions of retroactive interference were worse for field-independent than for field-dependent people (Miller, 1953). A number of similar studies have since appeared on the relationship between field dependence and proactive or retroactive interference effects (Gardner & Long, 1961;Kelley, 1964;Long, 1962;McKenna, 1967;Schuck, 1968;. Some of these studies have found a greater effect of retroactive interference among field-dependent subjects but some have not.…”
Section: Associative Learninmentioning
confidence: 98%
See 4 more Smart Citations
“…In contradiction to Gollin and Baron, a dissertation study appeared at about the same time in which savings scores on relearning under conditions of retroactive interference were worse for field-independent than for field-dependent people (Miller, 1953). A number of similar studies have since appeared on the relationship between field dependence and proactive or retroactive interference effects (Gardner & Long, 1961;Kelley, 1964;Long, 1962;McKenna, 1967;Schuck, 1968;. Some of these studies have found a greater effect of retroactive interference among field-dependent subjects but some have not.…”
Section: Associative Learninmentioning
confidence: 98%
“…These models assume that structuring is involved in a crucial way in some, but not in all associative learning situations. A number of similar studies have since appeared on the relationship between field dependence and proactive or retroactive interference effects (Gardner & Long, 1961;Kelley, 1964;Long, 1962;McKenna, 1967;Schuck, 1968;. Gallin and Baron (1954) suggested that the subjects who were most successful at resisting the effects of retroactive interference were those who could impose an appropriate organization on the items of the original and interpolated lists thereby keeping them functionally distinct.…”
Section: Associative Learninmentioning
confidence: 99%
See 3 more Smart Citations